Systemic lupus erythematosus presented as hemorrhagic pericardial effusion with cardiac tamponade: a case report - Ng, Fei Yin; Gew, Lai Teck; A., Pravindh; Hoo, Fan Kee (Synatom Research, 2014)
Hemorrhagic pericardial effusion with cardiac tamponade as the earliest clinical manifestation of systemic lupus erythematosus is distinctly uncommon. Hereby we report a case of a 42-year-old gentleman who presented to us with cardiac tamponade. Pericardiocentesis revealed a hemorrhagic pericardial effusion, which was later confirmed to be caused by systemic lupus erythematosus. He was started on oral corticosteroid and there was no recurrence over the eight months of follow up with a heumatologist.